Foreign body rectum: A case report - Panwar, Pradeep; Bagree, Rajendra; Jain, Richa; Shukla, Veena (Indian Journal of Case Reports, 2019)
Rectal foreign bodies are confronted frequently in a surgical emergency. These are often related to sexual behaviour. Due to the fear of social embarrassment, patients tend to hide the facts associated with the incident and present late. Because of the serious complications, foreign body rectum should be considered as an emergency and managed in a well-organised manner. Diagnosis can be made by clinical and radiological examination. In the majority of cases, the transanal approach is successful. Laparotomy is reserved for cases with perforation or peritonitis. Here, we report the case of a 24-year-old male who inserted an electrical beard trimmer in his rectum under alcohol intoxication. Since transanal removal failed, emergency laparotomy with successful removal of foreign body was done.